KONSUMSI MINUMAN HERBAL DAN PROBIOTIK DI KALANGAN MAHASISWA PADA MASA PANDEMI COVID-19 - Halim, Indah Oktavia; Rasmikayati, Elly; Saefudin, Bobby Rachmat (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Drinks are fluids that are needed by the body, these drinks are categorized into healthy drinks and sweet drinks. Drink consumption changed during the Covid-19 pandemic, which is a new virus originating from Wuhan, China with a very fast spread that has an impact on the economy, changes in social relations, and changes in lifestyle. Efforts that can be made to reduce the spread of the virus is to maintain the body's immunity, one way is by consuming healthy drinks. Although healthy drinks for students during the pandemic have increased, the consumption of sweet drinks is still favored by students and until now there are still few studies that discuss the habits of consuming healthy drinks in students. The purpose of this study was to determine  of consumption of healthy drinks both before and during the Covid-19 pandemic. This study uses a quantitative descriptive design with a survey method. The study was conducted on students of the Faculty of Agriculture, Padjadjaran University batch 2020. The analytical method used was descriptive statistics with column diagrams, frequency distribution tables and cross tabulations. The results showed that there was an increase in the consumption of healthy drinks, namely herbal drinks and probiotic drinks during the Covid-19 pandemic.